2001
DOI: 10.1183/09031936.01.17508720
|View full text |Cite
|
Sign up to set email alerts
|

Reduced late asthmatic response by repeated low-dose allergen exposure

Abstract: Reduced late asthmatic response by repeated low-dose allergen exposure. M. Palmqvist, Z-H. Cui, M. Sjöstrand, A. Lindén, J.Lötvall. #ERS Journals Ltd 2001. ABSTRACT: Allergic asthmatic individuals are often exposed to low-doses of allergen in their everyday life. Extended exposure to allergen has lead to down-regulation of the allergic process in cell systems and in animal models. The aim of this study was to evaluate whether any such inhibitory mechanism of allergic responses can be seen in man in vivo.Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
3
15
0
Order By: Relevance
“…In previous repeated low-dose allergen challenge studies, ICS-naïve asthmatics demonstrated small reductions in FEV1 immediately after allergen exposure (ranging from 6.50 to 9.2%) without any significant effect on FEV1 measured the next morning [16][17][18][25][26][27][28][29]; this is similar to our findings. However, these previous studies also demonstrated increased airway inflammation; FeNO, sputum measurements of eosinophils and sputum Th2 mediators increased after low-dose challenge [18,27,28].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In previous repeated low-dose allergen challenge studies, ICS-naïve asthmatics demonstrated small reductions in FEV1 immediately after allergen exposure (ranging from 6.50 to 9.2%) without any significant effect on FEV1 measured the next morning [16][17][18][25][26][27][28][29]; this is similar to our findings. However, these previous studies also demonstrated increased airway inflammation; FeNO, sputum measurements of eosinophils and sputum Th2 mediators increased after low-dose challenge [18,27,28].…”
Section: Discussionsupporting
confidence: 91%
“…The low-dose allergen challenge model has been developed in order to administer a more physiologically relevant concentration of allergen repetitively over a period of days. Low-dose allergen challenge increases airway inflammation and bronchial hyper-reactivity [15][16][17] and is inhibited by ICS and antileukotriene drugs in ICS-naïve asthma patients [15,18]. The low-dose allergen challenge model has not been evaluated in patients taking ICS.…”
Section: Introductionmentioning
confidence: 99%
“…In newborns and infants during the first year of life, failing to shift a Th2 cytokine profile to a Th1 profile has been associated with blood eosinophilia and serum markers of atopy (24). Others have demonstrated that there is no relationship between the number of eosinophils and an attenuated late asthmatic response with repeated low-dose allergen exposure (26). Therefore, investigation into the Th1/Th2 balance in very young mice outside of the BAL fluid compartment may help clarify the association between early life eosinophilia and a reduced later life allergic inflammatory response.…”
Section: Discussionmentioning
confidence: 95%
“…In this challenge setting, patients with atopic asthma were subjected to inhalations of fixed doses of allergen, titrated to cause minimal bronchoconstriction and administered once daily on 4-10 consecutive weekdays [1][2][3][4][5][6]. The procedure generates a distinct increase in airway hyperresponsiveness (AHR) to direct bronchoconstrictors [1][2][3][4][5][6].…”
mentioning
confidence: 99%